Measures of knee internal and external rotation made with a digital inclinometer are consistent with the measures made with an electromagnetic tracking system - Mark K. Timmons; Hunter G. Copley; Dustin T. Darnell; Seth T. Jude; Gary McIlvain (Journal of Experimental Orthopaedics)
Abstract Purpose Individuals with excessive knee rotation have higher levels of dysfunction and disability. An inexpensive, and reliable method to assess knee internal (IR) and external (ER) rotation will improve the assessment of knee injuries. The study explored the reliability and measurement error of two methods of knee rotation measurement. The study tested the hypothesis that the digital inclinometer will provide reliable measures of knee internal and external rotation and that the digital inclinometer measurements will be consistent with the measurements made with the electromagnetic tracking system. Methods Twenty (20) participants without knee injury participated. Knee IR and ER were measured using electromagnetic tracking and a digital inclinometer. The intraclass correlation coefficient (ICC(2,1)) was calculated for both techniques. Results The within device ICC values ranged from 0.826 to 0.939 for both devices. The within‐device minimal detectable change (MDC) ranged from 1.2° to 1.9°. The ICC values for EI and IR measures collapsed between the devices, ranged from 0.717 to 0.859. The MDC calculated between devices ranged from 1.6° to 1.9°. Conclusion The results of the current study show that knee IR and ER can be measured reliably with both measurement techniques. The measurement of knee ER and IR did not differ between the two devices or between the right and left sides. Level of Evidence Level IV, diagnostic, case series study.